Application of Progressive Muscle Relaxation and Deep Breathing in Working Pregnant Women to Reduce Stress Levels During the Covid-19 Pandemic - Dini Sri Sundari; Siswanto; Emiliana Primastuti (Future Science, 2023)
The COVID-19 pandemic has a considerable impact on the stress level of pregnant women, especially working pregnant women who are at risk of causing premature birth, hypertension in pregnant women, to maternal and fetal death. The purpose of this study was to determine the effect of using progressive muscle relaxation combined with deep breath relaxation on pregnant women working during a pandemic. This study used a one-group pretest and posttest design. There were five participants in this study with the criteria of working pregnant women in the third trimester of pregnancy. Samples were selected through a purposive sampling method and data analysis using a Paired T-Test test. The stress level measurement instrument uses the DASS 42 scale (Depression Anxiety Stress Scales 42). The results showed that there was a very significant effect of the use of progressive muscle relaxation and deep breath relaxation on the stress levels of working pregnant women. The implication of this study is to prove that the use of progressive muscle relaxation and deep breath relaxation has an effect on reducing the stress levels of pregnant women working during a pandemic. The limitation of this study is the lack of supporting data such as relationship with husband, workload, and difficulties experienced during pregnancy. For future research it is recommended to consider husband and family support as findings in the study. Other impacts of the application of progressive muscle relaxation and deep breath relaxation need to be further researched using appropriate measurement instruments to measure their effectiveness.